ADAPTASI STANDAR UNECE SEBAGAI BENTUK MODERNISASI OFFICIAL STATISTIC INDONESIA - Abduroqy Alimarwan Dunda (Komunitas Menulis dan Meneliti (Kolibi), 2023)
Modernization of official statistics is the role of BPS in improving the quality of statistical activities. The BPS framework states that modernizing official statistics can be done by meeting international standards and adapting international best practices. This article uses library research and internet searching methods to collect various information in adapting international practices used by BPS. Standard practices used by BPS include human resources, organizational framework and evaluation, statistical production, information methods and technology, data collection and data sources, dissemination and communication, standards and metadata.